QUALITY AND PRODUCTIVITY OF PEACH FRUITS AND WHITE CLOVER ESTABLISHMENT AS COVERAGE, INFLUENCED BY THE BORON APPLICATION - Rovedda, Luís Fernando; Blood, Renato Rezende Young; Motta, Antonio Carlos Vargas; Serrat, Beatriz Monte (Scientia Agraria, 2006)
There is little information about necessity of Boron application for peach (Prunus persica) orchards at South of Brazil. So, an experiment was installed to evaluate the response to B application at a five-year old commercial peach orchard, using Coral cultivar. The orchard was located at Campo do Tenente county, Parana state and managed under Integrated Production System. The treatments consisted of four B rates (0, 1, 2 and 4 kg of B.ha-1), applied during Fall on alley area. Yield, foliar analysis, and fruit quality (consistence, Brixo, caliber distribuition) for peach and growth for white clover (Trifolium repens) were obtained to evaluate the effect B application. To determine extractable B, soil samples were collected from two layers (0-20 and 20-40 cm), during three period (3, 9 and 15 months after B application). Each kg B/ha applied provided a linear increment of 0.31, 0.09 and 0.01 mg B.dm-3 within 0-20 cm and 0.27, 0.12 and 0.02 mg B.dm-3 within 20-40 cm depth, after 3, 6 and 9 months, respectively. These increments correspond 76, 28 and 5 % of B recovering within 0-40 cm depth for three sampling periods. Beneficial effect of B application was only observed for pulp consistency with higher value for the biggest B rate. Boron application did not result in change on the foliar concentration of macro and micronutrients evaluated. The white clover obtained increase in the percentage of cover area but without significant differences. In conclusion, B application had a low residual effect in the soil and enhanced the pulp.